Analisis Faktor yang Mempengaruhi Keselamatan Lalu Lintas pada Mobil Bak Terbuka di Jembatan Suramadu Madura - Purnomo Ari Wibowo; Agus Prasetyo (Lembaga Pengembangan Kinerja Dosen, 2024)
Research based on facts in the field, namely the problems caused by Traffic Safety on the Suramadu Bridge which are very complex, ranging from accidents, order, comfort and behavior of drivers using the Suramadu Bridge, especially drivers of goods vehicles, causing Traffic Safety on the Suramadu Bridge to be less than good. Caused by several factors including vehicle conditions, road conditions, and driver behavior so that traffic problems occur such as accidents caused by drivers of goods vehicles who violate regulations and act arbitrarily. The formulation of the problem, research objectives and hypotheses in this study are to analyze the positive and significant influence individually between the independent variables, namely vehicle conditions, road conditions, driver behavior on traffic safety on the Suramadu Bridge. The objects taken are drivers of goods vehicles crossing the Suramadu Bridge. This data source includes secondary and primary data with as many as 100 respondents who are drivers of goods vehicles on the Suramadu Bridge. Using multiple linear regression equation analysis techniques. The results show that there is a positive and significant influence partially between Vehicle conditions on Traffic Safety, Road conditions on Traffic Safety, Driver behavior on traffic safety. The coefficient of determination obtained an Adjusted R square value of 0.619%, thus the remaining 61.9% or 38.1% was caused by other factors.